A new Paracoccus species from Palaearctic region (Hemiptera, Sternorrhyncha, Coccoidea, Pseudococcidae) - Mazzeo, Gaetana; Franco, José Carlos; Russo, Agatino (Zootaxa, 2009)
A new mealybug species, Paracoccus leucadendri sp. nov., is described from Portugal. This is the first record of a Paracoccus species from Europe. It is suggested that its presence in Portugal is the result of a fortuitous introduction with its host plant, Leucadendron sp. (Proteaceae). An identification key is presented to distinguish this new Paracoccus species from other mealybug species reported on Proteaceae in the world.